Dakwah sebagai Sistem Manajemen Perubahan: Relevansi Konsep Hikmah, Halaqah, dan Sabr dalam Praktik Kepemimpinan Organisasi Kontemporer - Rohman (IDARI: Jurnal Manajemen Dakwah, 2026)
Contemporary change management literature notes that over 70 per cent of organisational transformation programmes fail to meet their targets, and that such failures are more often caused by human resistance than by strategic weaknesses. On the other hand, Islamic da’wah, as a system of social transformation, has successfully mobilised individuals and civilisations for over fourteen centuries without formal authority, without incentive budgets, and without coercive power. However, until now, da’wah has largely been positioned as an object managed by management science, rather than as a subject offering its own managerial logic. This article bridges that gap by analysing three core concepts of da’wah hikmah, halaqah, and sabr as coherent and operationalisable principles of change management within contemporary organisational leadership. This research employs a qualitative approach using an integrative-conceptual literature review method, combining primary Islamic sources, Western management theory, and contemporary da’wah management literature. The results of the analysis indicate that hikmah converges with situational leadership but transcends it by fostering genuine acceptance rather than mere formal compliance; halaqah converges with team learning and communities of practice but transcends them through a dimension of vertical accountability that deepens commitment; and sabr converges with strategic patience but transcends it through a transcendent source of energy that does not diminish under pressure. These three concepts are synthesised into the integrative Da’wah-Based Change Management (DBCM) model with the original proposition: the source of change energy determines the resilience of change. This model offers a theoretical contribution to the development of value-based da’wah management whilst serving as a practical framework for the management of da’wah institutions in Indonesia that are facing the challenges of professionalisation without losing the spirit of da’wah